Autophagy inhibition mediated by MCOLN1/TRPML1 suppresses cancer metastasis via regulating a ROS-driven TP53/p53 pathway. Issue 8 (3rd August 2022) - Xing, Yanhong; Wei, Xiangqing; Liu, Yucheng; Wang, Meng-Meng; Sui, Zhongheng; Wang, Xinyan; Zhu, Wucheng; Wu, Mengmei; Lu, Chen; Fei, Yuan-Hui; Jiang, Yi; Zhang, Yang; et al.
ABSTRACT: Compelling evidence has demonstrated that macroautophagy/autophagy plays an important role in regulating multiple steps of metastatic cascades; however, the precise role of autophagy in metastasis remains unclear. This study demonstrates that autophagy inhibition induced by MCOLN1/TRPML1 suppresses cancer metastasis by evoking the ROS-mediated TP53/p53 pathway. First, we found that MCOLN1-mediated autophagy inhibition not only profoundly inhibits both migration and invasion in malignant melanoma and glioma cell lines in vitro, but also suppresses melanoma metastasis in vivo . Second, our study reveals that autophagy inhibition induced by MCOLN1 leads to damaged mitochondria accumulation followed by large quantities of ROS release. Third, we demonstrate that the elevated ROS resulting from autophagy inhibition subsequently triggers TP53 activity, which in turn modulates expression of its downstream targets that are involved in a broad spectrum of the metastatic cascade to suppress metastasis including MMP members and TWIST. In summary, our findings have established a mechanism by which autophagy inhibition suppresses metastasis via the ROS-TP53 signaling pathway. More importantly, our study demonstrates that autophagy inhibition through stimulation of MCOLN1 could evidently be one of the therapeutic potentials for combating cancer metastasis. Abbreviations: 3-MA: 3-methyladenine; AA: amino acid; ATG5: autophagy related 5; ATG12: autophagy-related 12; Baf-A1: bafilomycin A1 ; CCCP: carbonyl cyanide m-chlorophenylhydrazone; CQ: chloroquine; DMEM: Dulbecco's Modified Eagle Medium; EMT: epithelial–mesenchymal transition; FBS: fetal bovine serum; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; HEK: human embryonic kidney; LAMP1: lysosomal-associated membrane protein 1; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MCOLN1/TRPML1: mucolipin TRP cation channel 1; MMP: matrix metallopeptidase; NC: negative control; NRK: normal rat kidney; PBS: phosphate-buffered saline; shRNA: short hairpin RNA; siRNA: short interfering RNA; SQSTM1/p62: sequestosome 1; ULK1: unc-51 like autophagy-activating kinase 1.